GERMINATION OF NUTMEG SEEDS (Myristica argentea Warb) IN VARIOUS MEDIA WITH SCARIFICATION TREATMENT (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
Nutmeg has considerable potential to enhance the local economy, especially in the Papua region, where it is primarily cultivated in the Fakfak Regency and commonly known as Fakfak Nutmeg. One of the major challenges in nutmeg cultivation is the extended seed germination period, which limits the availability of high-quality planting materials. Typically, untreated nutmeg seeds germinate within 2 to 3 months after planting, whereas scarified seeds germinate more quickly, in approximately 1.5 months. This study aimed to evaluate the effects of different growth media and seed coat scarification on nutmeg seed germination. A randomized factorial design was employed, with seed coat treatment and growth medium. The observed variables included germination percentage, germination rate, peak value, average daily germination, seedling height, number of leaves, number of roots, and stem weight. The results showed that scarification had a significant effect on germination, particularly in terms of germination percentage, average daily germination, germination rate, and peak value. However, it did not significantly affect other growth parameters such as seedling height, number of leaves, number of roots, or stem weight. No significant differences in germination performance were observed between sand and soil media.